2022
DOI: 10.1002/cbic.202200327
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 Papain‐Like Protease: Structure, Function and Inhibition

Abstract: Emerging variants of SARS-CoV-2 and potential novel epidemic coronaviruses underline the importance of investigating various viral proteins as potential drug targets. The papain-like protease of coronaviruses has been less explored than other viral proteins; however, its substantive role in viral replication and impact on the host immune response make it a suitable target to study. This review article focuses on the structure and function of the papain-like protease (PL pro ) of SARS-CoV-2, including variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“… 313 GRL0617, developed by Ratia et al., was originally used as an inhibitor of SARS‐CoV‐1 PLpro and recently was investigated as an inhibitor of SARS‐CoV‐2 PLpro. 314 A drug‐repurposing screening, carried out using a MedChemExpress bioactive compound library, identified tropifexor as a novel and promising PLpro inhibitor against SARS‐CoV‐2. 315 Recently, through virtual screening of the US FDA‐approved drug library, nine compounds were identified and in vitro biochemical and cell culture‐based studies revealed anti‐SARS‐CoV‐2 PLpro activity of mefloquine and lopinavir.…”
Section: Repurposing Clinically Available Drugs and Therapies For Pat...mentioning
confidence: 99%
“… 313 GRL0617, developed by Ratia et al., was originally used as an inhibitor of SARS‐CoV‐1 PLpro and recently was investigated as an inhibitor of SARS‐CoV‐2 PLpro. 314 A drug‐repurposing screening, carried out using a MedChemExpress bioactive compound library, identified tropifexor as a novel and promising PLpro inhibitor against SARS‐CoV‐2. 315 Recently, through virtual screening of the US FDA‐approved drug library, nine compounds were identified and in vitro biochemical and cell culture‐based studies revealed anti‐SARS‐CoV‐2 PLpro activity of mefloquine and lopinavir.…”
Section: Repurposing Clinically Available Drugs and Therapies For Pat...mentioning
confidence: 99%
“…SARS-CoV-2 encodes two cysteine proteases—first, the main protease, and then the papain-like protease [ 58 ]. These papain-like proteins have a role in viral replication (such as in the cleavage of viral proteins) and a role in the host immune response [ 58 , 59 ]. Ebselen was identified as a nonspecific cysteine modifier and a main and papain-like protease inhibitor [ 58 , 60 ].…”
Section: Repurposing Of Drugs For Treatment Of Covid-19mentioning
confidence: 99%
“…PL pro is another essential SARS-CoV-2 Cys protease because it cleaves three pro-proteins into their mature forms: Nsp1, Nsp2, and Nsp3 [ 41 ]. The related PL pro from SARS-CoV-1 (causative agent of SARS) has additional roles related to its canonical proteolytic activity, including deubiquitination and deISGylation [ 42 , 43 ], some of which appear to be shared by the 83% identical PL pro from SARS-CoV-2 [ 44 46 ].…”
Section: Cysteine Residues In Enzyme Catalysis: Sars-cov-2 Proteasesmentioning
confidence: 99%